2016
DOI: 10.1016/j.tins.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Warning! Dopaminergic Modulation of the Superior Colliculus

Abstract: Recent work by Bolton et al. describes a dopaminergic input to the superior colliculus (SC) from the zona incerta, as well as the organization of D1- and D2-receptor expression in the SC. We discuss a potential role for this input in modulating SC-mediated behavior, particularly in response to aversive stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The special lack of correlations for 18 F-fallypride uptake in the colliculi also points towards a functional separation of dopamine neurons that project to the colliculi compared to other target regions. Both of these ideas are consistent with the seemingly specific role for dopamine signalling in the colliculi in behavioural responses to aversive or fearful stimuli [15] [16]. Our experiment examined well-handled subjects in a nonfearful environment.…”
Section: Resultssupporting
confidence: 82%
“…The special lack of correlations for 18 F-fallypride uptake in the colliculi also points towards a functional separation of dopamine neurons that project to the colliculi compared to other target regions. Both of these ideas are consistent with the seemingly specific role for dopamine signalling in the colliculi in behavioural responses to aversive or fearful stimuli [15] [16]. Our experiment examined well-handled subjects in a nonfearful environment.…”
Section: Resultssupporting
confidence: 82%
“…Recent studies in our laboratory showed that intranasal dopamine application reduced escape behavior in two tests of unconditioned fear (i.e., escape from bright light and ultrasonic vocalization response to immobilization) 80 , attenuated footshock-induced freezing in training, test, and retest sessions in fear extinction conditioning, and reduced PSF following electrical stimulation of the dPAG at the escape threshold 81 . Dopamine neurons in the zona incerta (A13 zone) have been suggested to be the possible source of dopaminergic input that is involved in modulating the neural substrates of fear in the midbrain tectum 82,83 .…”
Section: Pharmacological Strategies To Inhibit the Transfer Of Aversimentioning
confidence: 99%
“…To assess which ZI neuron type(s) contribute to fear-memory conditioning, we injected double-floxed, Cre-dependent TetTox into the ZI of Cre-driver mouse lines expressing Crerecombinase selectively in tyrosine hydroxylase-positive (TH + ), somatostatin-positive (SST + ) or parvalbumin-positive (PV + ) neurons. TH + -neurons of the ZI were proposed to modulate responses to aversive stimuli 16 ; however, silencing ZI TH + -neurons caused no significant impairment of fear conditioning (Figure 1i-1l). SST + -neurons in the ZI are thought to function in cortical neuronal development 17 .…”
mentioning
confidence: 99%